Malawi Economic Monitor, March 2015 : Managing Fiscal Pressures - World Bank (World Bank, Lilongwe, 2015)
The aim of the Malawi Economic Monitor (MEM) is to foster better informed policy analysis and debate regarding the key challenges that Malawi needs to address in order to achieve high rates of stable, inclusive and sustainable economic growth. The MEM has two parts: Part 1 presents a review of recent economic developments, followed by a macroeconomic outlook; and Part 2 focuses on a selected topic key to Malawi s development prospects. The special topic of this edition is on building trade competitiveness.